A biocomputational platform for the automated construction of large-scale mathematical models of miRNA-transcription factor networks for studies on gene dosage compensation - Acón Chan, Man Sai (2016)
Cancer complexity and resistance is mediated by cell-to-cell heterogeneity, which is the consequence of the enormous instability of its genetic material. It is unknown how cancer cells are able to withstand the effects of these alterations, while normal cells are typically very sensitive. We hypothesize that cancer requires specific type of stability to survive the enormous chromosomal alterations. This stability may be mediated by a group of genes, whose expression is tightly regulated to maintain viability through a process called gene dosage compensation. This mechanism could be mediated by systems-level properties of complex networks of microRNAs (miRNA) and transcription factors (TF), regulating gene expression despite changes in copy number. Therefore, we designed a biocomputational platform to automatically construct large-scale mathematical models regulating the expression of several candidate genes under dosage compensation. This platform has a broader potential application to other scientific questions involving miRNA and TF networks.